Learning from Participatory Design Practices With Urban Indigenous Communities In Chile And Aotearoa, New Zealand - Ivelic, Iván; Mortensen Steagall, Marcos (Translator) (Tuwhera)
Co-housing and communal living are gaining increasing attention worldwide as they offer significant social and environmental benefits. Historically, most Indigenous communities worldwide have lived in communal dwellings with intergenerational ties, shared resources, and deep connections to the land and nature. However, many of these populations have been displaced from their ancestral lands and communities and now live in homes and neighborhoods that do not reflect their values, traditions, and worldviews. In recent decades, increasing efforts have been to recover these original values and translate them into contemporary community housing through participatory design processes. There is little literature that examines contemporary housing co-designed with Indigenous communities from an international perspective. This article presents the results of research conducted in New Zealand and Chile on participatory practices in the co-design of collective housing with Indigenous communities, based on a literature review and interviews with the designers of one of the emblematic cases in Chile where Indigenous values have been integrated into social housing through co-design processes with the intercultural community that inhabits it.